2021
DOI: 10.3390/nu13072319
|View full text |Cite
|
Sign up to set email alerts
|

Southwest Harvest for Health: An Adapted Mentored Vegetable Gardening Intervention for Cancer Survivors

Abstract: Harvest for Health is a home-based vegetable gardening intervention that pairs cancer survivors with Master Gardeners from the Cooperative Extension System. Initially developed and tested in Alabama, the program was adapted for the different climate, growing conditions, and population in New Mexico. This paper chronicles the feasibility, acceptability, and preliminary efficacy of “Southwest Harvest for Health”. During the nine-month single-arm trial, 30 cancer survivor-Master Gardener dyads worked together to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In addition, ACES reduced the cost of Master Gardener credentialling by 25% and fundraising efforts through UAB have resulted in further scholarships to cancer survivors who have completed the program. As Harvest for Health initially began as a small pilot study, it is understandable that stakeholders may have considered the program transient; however, it has grown over time to a statewide initiative, and is currently being evaluated in the Southwest [ 25 , 26 ]. To facilitate further dissemination to other regions of the country, with the goal of eventually expanding nationwide, a long-term stable funding mechanism will need to be put in place.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ACES reduced the cost of Master Gardener credentialling by 25% and fundraising efforts through UAB have resulted in further scholarships to cancer survivors who have completed the program. As Harvest for Health initially began as a small pilot study, it is understandable that stakeholders may have considered the program transient; however, it has grown over time to a statewide initiative, and is currently being evaluated in the Southwest [ 25 , 26 ]. To facilitate further dissemination to other regions of the country, with the goal of eventually expanding nationwide, a long-term stable funding mechanism will need to be put in place.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported better socialization and social cohesion associated with gardening, perhaps due to collectively maintaining a garden, sharing produce, and discussing optimal growing strategies [ 62 , 65 ]. Gardening activities, classified as low-to-moderate-intensity PA [ 68 , 69 , 70 ], are associated with higher PA levels [ 63 , 66 ] and may serve as a gateway to additional types of PA, such as yard work, walking, or joining a gym [ 18 , 21 ]. Additionally, gardening activities can involve both upper and lower body functions such as kneeling, bending, lifting, reaching, and the use of small gardening tools.…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggest that tending a home-based vegetable garden can result in meaningful increases in vegetable intake, PA, and improvements in QOL [ 18 , 20 ], especially physical function. We adapted the intervention to suit the different climate and growing conditions in New Mexico [ 21 , 22 ]. The Southwest Harvest for Health feasibility study was launched in February 2020, concurrent with the emergence of COVID-19 in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, clinical decision support systems 75 and web-based lifestyle interventions 76,77 for cancer survivors are a promising treatment option due to being both affordable and accessible. Despite challenges due to the COVID-19 pandemic, the home-based vegetable gardening program is feasible, wellreceived, and may result in increased V and F consumption among cancer survivors 78 .…”
Section: Novel Strategies For Management Of Cancer In the Covid-19 Eramentioning
confidence: 99%